The Anastasian Military Decree from Perge in Pamphylia: Revised 2nd Edition - Fatih Onur (Gephyra, 2017)
This article contains a revised version of the inscription from Perge containing a military decree of Anastasius I. The fragments of this inscription were unearthed in 1974 during excavations at Perge. The inscription was discovered in about 850 fragments in an area to the south of northern fountain on the southern slopes of the acropolis. Today these fragments are preserved in the storage rooms of the Museum of Antalya. It contains an imperial sermo, an enactment of a magister militum, both translated from Latin into Greek, and a notitia concerning the number of soldiers in a legio and their respective salaries in kind and in cash.The main issue addressed in the inscription concerns the soldiers in a legio and that they have been deprived of their customary payments and retirement bounties on account of corruption and the sale of posts within the unit and its constituent scholae. In particular, that the names of the deceased or of missing soldiers had not been removed from the regimental records or their positions had been filled by unqualified or ineligible men who had obtained these posts through either bribery or influence. Accordingly, this edict aims to impose measures against these corrupt practices. Anastasius orders that the actual numbers of soldiers holding each grade in the legio should be investigated and any shortfall was to be rectified and it was to be maintained at a full complement in accordance with the schedule of grades and annonae provided.